In Vitro Activity of Ertapenem versus Ceftriaxone against Neisseria gonorrhoeae Isolates with Highly Diverse Ceftriaxone MIC Values and Effects of Ceftriaxone Resistance Determinants: Ertapenem for Treatment of Gonorrhea? - Unemo, Magnus (American Society for Microbiology, 2012)
Clinical resistance to the currently recommended extended-spectrum cephalosporins (ESCs), the last remaining treatment options for gonorrhea, is being reported. Gonorrhea may become untreatable, and new treatment options are crucial. We investigated the in vitro activity of ertapenem, relative to ceftriaxone, against N. gonorrhoeae isolates and the effects of ESC resistance determinants on ertapenem. MICs were determined using agar dilution technique or Etest for international reference strains (n = 17) and clinical N. gonorrhoeae isolates (n = 257), which included the two extensively drug-resistant (XDR) strains H041 and F89 and additional isolates with high ESC MICs, clinical ESC resistance, and other types of clinical high-level and multidrug resistance (MDR). Genetic resistance determinants for ESCs (penA, mtrR, and penB) were sequenced. In general, the MICs of ertapenem (MIC(50) = 0.032 μg/ml; MIC(90) = 0.064 μg/ml) paralleled those of ceftriaxone (MIC(50) = 0.032 μg/ml; MIC(90) = 0.125 μg/ml). The ESC resistance determinants mainly increased the ertapenem MIC and ceftriaxone MIC at similar levels. However, the MIC ranges for ertapenem (0.002 to 0.125 μg/ml) and ceftriaxone (<0.002 to 4 μg/ml) differed, and the four (1.5%) ceftriaxone-resistant isolates (MIC = 0.5 to 4 μg/ml) had ertapenem MICs of 0.016 to 0.064 μg/ml. Accordingly, ertapenem had in vitro advantages over ceftriaxone for isolates with ceftriaxone resistance. These in vitro results suggest that ertapenem might be an effective treatment option for gonorrhea, particularly for the currently identified ESC-resistant cases and possibly in a dual antimicrobial therapy regimen. However, further knowledge regarding the genetic determinants (and their evolution) conferring resistance to both antimicrobials, and clear correlates between genetic and phenotypic laboratory parameters and clinical treatment outcomes, is essential.